2010
DOI: 10.1016/j.jvs.2010.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia limits experimental aortic aneurysm progression

Abstract: Objective Diabetes mellitus (DM) is associated with reduced progression of abdominal aortic aneurysm (AAA) disease. Mechanisms responsible for this negative association remain unknown. We created AAAs in hyperglycemic mice to examine the influence of serum glucose concentration on experimental aneurysm progression. Methods Aortic aneurysms were induced in hyperglycemic (DM) and normoglycemic models by using intra-aortic porcine pancreatic elastase (PPE) infusion in C57BL/6 mice or by systemic infusion of ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 42 publications
4
103
1
Order By: Relevance
“…Future material testing of AAAs should seek to correlate overall changes in anisotropy and stiffness with mass fractions as well as collagen fibre diameter, undulation, orientation and cross-linking. Indeed, evidence suggests that diabetes tends to reduce the occurrence, expansion rate and rupture risk of AAAs [48,49], possibly through increased non-enzymatic cross-linking of collagen and/or other effects of hyperglycaemia, while overexpression of the cross-linking enzyme lysyl oxidase has been shown to protect mice from AAA development [50].…”
Section: Discussionmentioning
confidence: 99%
“…Future material testing of AAAs should seek to correlate overall changes in anisotropy and stiffness with mass fractions as well as collagen fibre diameter, undulation, orientation and cross-linking. Indeed, evidence suggests that diabetes tends to reduce the occurrence, expansion rate and rupture risk of AAAs [48,49], possibly through increased non-enzymatic cross-linking of collagen and/or other effects of hyperglycaemia, while overexpression of the cross-linking enzyme lysyl oxidase has been shown to protect mice from AAA development [50].…”
Section: Discussionmentioning
confidence: 99%
“…By intracoronary ultrasound, researchers found that diabetics with atherosclerosis have less compensatory coronary artery enlargement than non-diabetics and the researchers considered it can explain the diffuse and accelerated course of coronary artery disease in these patients (38). Patients with a longer duration of diabetes who were treated with insulin had (paradoxically) less reference segment and stenosis plaque accumulation and hyperglycemia increases plasminogen activator inhibitor 1 expression and attenuates AAA diameter had been demonstrated by animal experimental studies (39,40), lowering of serum glucose levels with insulin treatment diminishes this protective effect (41). Other researchers argued that diabetes promotes negative arterial wall remodeling or at least impairs compensatory arterial enlargement during the course of the atherosclerotic process (10).…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant reduction in aortic diameter was seen in DM-AAA mice compared to controls ( p = 0.047). Aortic medial neovascularity has been shown to play a role in aneurysm pathogenesis via its close involvement with MMP activation in the proteolytic degradation of the aortic wall [50, 51]. This study showed a decrease in neovessel density, macrophage infiltration and MMP-9 levels, demonstrating hyperglycemia to be protective against the formation of an aneurysm.…”
Section: Specific Impact Of Diabetes On Aaamentioning
confidence: 59%
“…Miyama et al [50] investigated the role of hyperglycemia on aortic diameter, medial neovascularity and MMP-9 level. A statistically significant reduction in aortic diameter was seen in DM-AAA mice compared to controls ( p = 0.047).…”
Section: Specific Impact Of Diabetes On Aaamentioning
confidence: 99%